Problematic Information Technology Innovations and the Rate of Justice Investment: The Judicious Impact of CEO Inducement and Association Anxieties - Ahmed, Sarfaraz; Kumaran, T. Senthil (International Journal of Supply Chain Management, 2018)
Problematic data innovation advancements display openings, as well as cause indeterminate effects on firm hazard that influences the value financing expense of a firm. This paper utilized longitudinal information from one-forty-six united states recorded firms that received radio recurrence ID (RFID), a problematic innovation that empowers inventory network prepare development. Results demonstrate that organizations that embraced RFID essentially diminished their cost of value capital, and the decrease was more grounded for firms with more noteworthy CEO motivating force based remuneration and coercive weight. The discoveries enable directors to make systems that expand the advantages of troublesome IT developments.